2015
DOI: 10.1016/j.applthermaleng.2014.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic analysis of a CO2 capture plant integrated with a commercial scale combined cycle gas turbine (CCGT) power plant

Abstract: In this study, a combined cycle gas turbine (CCGT) power plant and a CO2 capture plant have been modeled in GateCycle ® and in Aspen Plus ® environments respectively. The capture plant model is validated with experimental data from the pilot plant at the University of Texas at Austin and then has been scaled up to meet the requirement of the 427 MWe CCGT power plant. A techno-economical evaluation study has been performed with the capture plant model integrated with flue gas pre-processing and CO2 compression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…We note that our results are in good agreement with those of DECC. Further, these results also show good agreement with the recent work of Canepa and Wang (Canepa & Wang, 2015).…”
Section: Levelised Cost Of Electricity With and Without Pccsupporting
confidence: 82%
“…We note that our results are in good agreement with those of DECC. Further, these results also show good agreement with the recent work of Canepa and Wang (Canepa & Wang, 2015).…”
Section: Levelised Cost Of Electricity With and Without Pccsupporting
confidence: 82%
“…Ferreira and Balestieri performed technical and economic analysis of black‐liquor gasification cycle integrated with CO 2 capture system. Canepa and Wang designed and modeled a combined power‐plant based on technoeconomical evaluation. It was reported that the electricity cost could be decreased by optimizing the design parameters.…”
Section: Introductionmentioning
confidence: 99%
“…To include economic variables for cost reduction, the exergoeconomic analysis assign monetary costs to all energy streams (exergy costing), as well as to the exergy destruction incurred within each equipment of a system [13]. A techno-economic evaluation was performed for a combined cycle gas turbine power plant and a CO 2 capture unit, modeled using Aspen Plus V R [16]. Finally, exergoeconomic analysis has been used to evaluate a power plant with chemical looping combustion for CO 2 capture [15].…”
Section: Introductionmentioning
confidence: 99%